Macroeconomic policy at the end of the age of abundance - Jo Michell (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
Progressive policy proposals influenced by post-Keynesian economics emphasise the use of fiscal policy and income redistribution to maintain aggregate demand at levels which achieve full employment. Given persistent evidence of weak demand, excess capacity and unemployment in rich economies since around 1980, expansion of demand would have been appropriate over much of this period. Tighter supply constraints – both short-run constraints due to disruption caused by climate change and geopolitical tensions, and longer-run constraints due to absolute carbon budgets – impose additional challenges in designing policy. In order to increase investment sufficiently to achieve net zero goals, constraints on consumption may be required. Such constraints would weaken the multiplier mechanisms emphasised by post-Keynesian analysis, implying lower growth and higher public debt stocks. Traditional progressive policy proposals will need updating to reflect these constraints. New institutional arrangements will be required to implement updated policy packages.
Keywords: E12; E22; E31; E62; 330; macroeconomics; post-Keynesian economics; supply constraints; climate change